Market-based approaches to improving the safety of pork in Vietnam - International Livestock Research Institute (International Livestock Research Institute, 2020)
These are the highlights of the SafePORK project - 'Market-based approaches to improving the safety of pork in Vietnam' - from 2017–2019. In Vietnam, pork is the most widely consumed meat and nearly all is sold in millions of people via traditional (wet) markets. Yet, food hazards are pervasive, food scares common, trust in food low and enforcement capacity weak. This research, funded by the Australian Centre for International Agricultural Research (ACIAR), aimed to improve food safety while safeguarding livelihoods in the pork sector.